Mapping food availability and food scarcity in migrants’ hometown - Didit Purnomo; Indah Susilowati; F. X. Sugiyanto (Universitas Islam Indonesia, 2014)
The research aims to map and analyze food scarcity or surplus based on the food availability at migrant area in Wonogiri, Central Java. The rapid rural assessment and focus group discussion were used for detecting and exploring any food plant that is good and appropriate to the characteristics of migrant area. The condition of food availability in the Wonogiri regency could be stated to be surplus. The highest surplus was located in Giriwono sub-district and the lowest surplus in Bulukerto sub-district. Most of the sub-districts in Wonogiri subdistricts reached an IFI score < 0.5 (index of composite food security) in whichit could represent a secure condition.